A Characterisation of Organically Modified Polymers - Rodica CHIHAI (PEȚU); Claudia Veronica UNGUREANU; Vasile BRIA; Adrian CÎRCIUMARU (ACROSS)
Epoxy resins have many attractive properties, such as solvent and chemical resistance, low shrinkage, ease of cure and processing, good adhesive strength, excellent electrical and mechanical properties and ease of modification to optimize their features. These epoxy resins have been widely used as adhesives, surface coatings, aerospace composite matrix, laminates, membranes, pottings, encapsulants for semiconductors and insulating material for electronic devices. However, these systems do have some environmental problems. One problem of epoxy resins is that all the curing agents are still environmentally unfriendly and toxic before the cure. Therefore, the development of environmentally friendly epoxy systems has a great importance for designing the green and biocompatible materials used in many applications. For this study, two protein substances, gelatine and wheat gluten, were used to change the basic properties of three types of epoxy resin. Protein polymers are natural macromolecules derived from plants and animals, which make them an easily obtainable and renewable resource. The main purpose of this study was to determine the modifications of epoxy resins basic properties induced by organic modification agents. To highlight the effect of these proteins in an epoxy matrix, the mechanical tests, such as three-point bending and tensile were performed.